VD_FINDINFO MP / 2016 / 8 vom 6. Dezember 2016 - VD Tribunal cantonal (2016)
INSTANCE UNIQUE, MESURE PROVISIONNELLE, CONCURRENCE DÉLOYALE, RISQUE DE CONFUSION | 2 LCD, 3 al. 1 let. d LCD, 3 al. 1 let. e LCD, 261 CPC (CH), 5 CPC (CH)